Calculation Of Economic Well-Being Using Nonparametric Approach - Vondrová, Andrea; Nežinský, Eduard (European Scientific Journal, ESJ, 2016)
The aim of this paper is to present the analysis of measurement of economic well-being by the index of economic well-being for selected OECD countries. The report also outlines trends in the four domains of economic well-being that create the index. The domains are consumption, wealth, economic equality, and economic security. Furthermore, the paper offers an analysis of the sensitivity of our results to the choice of weights assigned by means of data envelopment analysis (DEA) model to these four domains and a description of the performance of the index of economic well-being compared to GDP per capita through the most recent recession that caused declines in both, real GDP per capita and the index of economic well-being.